Tinjauan Etika Bisnis Islam dalam Praktik Jual Beli Komoditas Karet di Desa Gurun Tuo, Kecamatan Mandiangin - Rana Puan Anjelina; Kemas Imron Rosadi; Firman Syah Noor (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The practice of buying and selling rubber commodities in Gurun Tuo Village has not fully aligned with Islamic business ethics principles, particularly regarding honesty (ṣidq), gharar (uncertainty), and justice (‘adl). This condition has the potential to disadvantage one of the parties, especially farmers as the main producers. Therefore, this study aims to analyze the practice of rubber trading and assess its conformity with the principles of Islamic business ethics. This research employed a qualitative approach using observation, interviews, and documentation as data collection techniques. Rubber farmers, collectors, and other related parties in Gurun Tuo Village were selected as informants. The collected data were analyzed descriptively to describe the actual conditions in the field. The results showed that several practices were still inconsistent with Islamic business ethics principles, such as the lack of transparency in determining quality and prices, the presence of gharar elements in the weighing process, and inequality in price determination that affected fairness for farmers. Nevertheless, some business actors had attempted to implement honesty in transactions. This study concludes that the practice of rubber commodity trading in Gurun Tuo Village has not fully complied with Islamic business ethics principles, especially in terms of honesty (ṣidq), justice (‘adl), and the prohibition of gharar. Factors influencing these conditions include internal factors such as socio-cultural, economic, and educational aspects, as well as external factors in the form of weak village institutions. However, the implementation of Islamic business ethics can be improved through transparency, education, and strengthening institutions such as cooperatives.